Решетка нормальных подгрупп группы локальных изометрий границы сферически однородного дерева - Лавренюк, Я.В.; Сущанский, В.И. (Український математичний журнал, 2008)
Наведено опис ґратки нормальних підгруп групи локальних ізомєтрій границі сферично однорідного дерева LIsom ∂T. Доведено, що кожен нормальний дільник цієї групи містить її комутант. Охарактеризовано фактор-групу групи LIsom dT за її комутантом. The structure of the normal subgroup lattice of the locally isometry group of the boundary of
spherically homogeneous tree LIsom ∂T is described. It is proved that every normal subgroup of
this group contains a commutant of LIsom ∂T. The quotient group of LIsom ∂T is characterized
by its commutant.